PELAKSANAAN ASESMEN DIAGNOSTIK DI GUGUS V KINTAMANI DALAM PEMBELAJARAN IPS - Pujiani, Ni Luh Nopi; I Wayan Lasmawan; I Wayan Kertih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to determine; teacher understanding, to determine whether teachers are able to compile, and whether teachers implement diagnostic assessments in grade IV of elementary school in social studies subjects. This research method is descriptive qualitative. Data collection techniques are through interviews, document studies, and observations. The subjects of the study were teachers, principals, and students at elementary schools in Kintamani. Based on data analysis of teacher understanding from 9 teachers, there were 5 teachers who understood very well, 3 teachers understood, and 1 teacher did not understand well. The number of principals who understood was 5 people, 2 principals understood, and 2 principals understood quite well. The number of teachers who always compiled diagnostic assessments and implemented diagnostic assessments was 5 people, teachers who sometimes implemented diagnostic assessments were 3 people, and the number of teachers who never conducted diagnostic assessments was 1 person. Of the 10 students who obtained very good cognitive assessment results, 5 people, 2 students obtained good, 1 student obtained a fairly good category, and 2 students were not good. Students who had very good physical conditions were 10 students. In terms of mental condition, there are 8 students in the very good category and 2 students in the quite good category. In terms of learning motivation, there are 5 students in the very good category, 3 students in the less good category and 2 students in the less good category have less good motivation. The conclusion from the results of this study is that teachers who do not understand and do not make diagnostic assessments are teachers who do not follow the training properly and do not know the technology and those who have carried out diagnostic assessments are teachers who have followed the training and are able to use technology.